Living Hadis dalam Konteks Sosial-Budaya - Ulzana Nurlian Nawa; Nawir Yuslem; Ardiansyah Ardiansyah (Student Research Journal, 2026)
This study is motivated by the rapid proliferation of hadith dissemination in the digital era, which has Living hadith in a socio-cultural context is a contemporary approach in hadith studies that emphasizes how the traditions of Prophet Muhammad SAW are practiced, internalized, and brought to life within society. This study does not only focus on textual aspects such as sanad (chain of transmission) and matn (text), but also on its practical manifestations in the form of traditions, rituals, and local culture. This paper aims to analyze the epistemology of living hadith, examine the theoretical frameworks utilized, and observe its relevance in modern society, particularly within Muslim communities. The research method employed is qualitative with a descriptive-analytical approach based on a literature review. The findings indicate that living hadith serves as a bridge between normative texts and dynamic empirical reality. In practice, living hadith manifests in oral traditions such as lectures and religious advice, written traditions like hadith calligraphy, and practical traditions like tahlilan and grave visitation (ziarah kubur). Thus, living hadith allows Islamic teachings to remain contextual, adaptive, and relevant in facing modern socio-cultural transformations.